Examining acute pelvic pains among patients in two selected hospitals in in the western Region of Ghana - Acquaye, Rosemary; Gyamfi, Abraham (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Pelvic pain is one of the commonest Out-Patient Department (OPD) cases in most hospital. Comparably, women experience pains in one or two parts of the body which may be due to excess stretch of the muscles, minor or major accidents and old age than men. The main objective of the study was to examine acute pelvic pains among patients in the Effia-Nkwanta and European hospitals in Takoradi. Descriptive survey was employed for the study. The population of the study comprises all patients who were undergoing pelvic ultrasound at Effia-Nkwanta and European hospitals in Takoradi as part of their management plan for pelvic disease or pain. A purposive sampling technique convenience sampling were used to select 400 patients for the study. The study employed the collection of previous pelvic ultrasound reports and reports obtained during the time of the study to obtain the data from the Radiologic Department at select hospitals with the SAL-30 A (Toshiba, Japan) and Philips Clear Vue real time ultrasound machines. The study found out that females are prone to pelvic pain than males, the most common presenting pathologies that cause pelvic pain are uterine fibroid, PID, Ectopic pregnancy, follicular cyst, BPH, Cystitis, colitis and Appendicitis and the organs that are mostly affected in cases of pelvic pain are uterus, ovaries, prostate, colon and bladder. It was therefore recommended that patients should be educated and encouraged to report to the hospital when there is any sign or symptom of pelvic pain.